Upaya Perpustakaan Perguruan Tinggi dalam Menciptakan Ruang Publik : Kajian “Wifi Zone Corner” Di Perpustakaan ITS - Astutik Nur Qomariyah; Lailatur Rahmi (IAIN Ponorogo, 2017)
This study intends to identify and analyze the efforts of the university library to create a public sphere. The study location is Wifi Zone Corner at ITS (Institut Teknologi Sepuluh Nopember) Library. This study used qualitative approach with descriptive method. The study results shows that the ITS Library has made efforts to create Wifi Zone Corner as a public sphere: (1) change the Wifi Zone Corner design into a public sphere become accessible, comfortable and without any binding rules; (2) held routine and non-routine activities with the concept of a public forum; and (3) make cooperation with some other institutions.